Enhancing internal audit quality through data analytics and transformational leadership - Fitria, Rahmadhianti Nur; Sitorus, Laurenza; Arianisari, Nabilla; Saproni, Saproni (Educoretax, 2025)
This study aims to examine the effects of data analytics and transformational leadership on internal audit report quality at the Financial and Development Supervisory Agency (BPKP) in Indonesia. The population consists of all auditors at BPKP, and a purposive sampling technique was employed to select 127 auditors as the sample. Data were collected using a structured questionnaire and analyzed with structural equation modeling using SmartPLS 4. The results show that data analytics and transformational leadership have a positive and significant effect on internal audit report quality. Therefore, organizations are encouraged to invest in both data analytics capabilities and transformational leadership development to maximize the quality of internal audit results.